The effect of RRA treatment on mechanical properties and wear behavior in vanadium micro-alloyed Hadfield's steel - Rui Wang; Wen Zhang; Fei Zhang; Hao Fu; Qinyuan Huang; Hong Wu; Zulai Li; Quan Shan (Journal of Materials Research and Technology, 2023)
To solve the ongoing problems of micro-alloyed Hadfield's steel, insufficient hardness and excessive deformation in the early working period, expensive alloying elements like Ti, Nb, and V have been utilized. However, traditional long-time, single-stage aging exacer-bates vanadium to assemble at the edge of initial precipitates, which diminishes estimated effects. For this, here we report the tremendous impact of retrogression and re-aging process (RRA) in this steel by booming the V (C, N) mean sized in 11 nm. The procedure enhances the micro-hardness, yielding strength, tensile strength, and impact-wear resistance for more than 27.4%, 29.5%, 22.2%, and 51.5%, respectively. Moreover, the wear mechanism of RRA samples has been investigated in that micro-sized precipitates surrounded by numerous nano V (C, N) stick in the matrix and hinder the abrasive embedding consistently, thus decreasing the micro-cutting and micro-plowing. This new process maximizes the utilization of costly and nonrenewable vanadium and magnifies the impact-wear resistance under either mild or medium-intensity working conditions.